Color memory as a diagnostic test for mild cognitive impairment and early stage of Alzheimer’s disease - Vaiva Sutnikiene; Egle Audronyte; Gyte Pakulaite-Kazliene; Gintaras Kaubrys (Frontiers in Neurology)
BackgroundColor vision and memory are potential markers of Alzheimer’s disease (AD); however, information regarding their changes in early AD remains limited.ObjectiveThe aim of this study was to evaluate color recognition memory in mild cognitive impairment (MCI), early Alzheimer’s disease (AD), and older adults with normal cognition, as well as to assess its diagnostic properties.MethodsWe included 27 participants with mild dementia (MD), 25 with MCI, and 25 older adults with normal cognition who served as the control group (CG). Participants completed the Mini-Mental Status Examination (MMSE), the Clinical Dementia Rating (CDR), and the Alzheimer’s disease Assessment Scale-Cognitive Subscale (ADAS-Cog 13) for cognitive assessment; delayed word recall (after 30 min), the Ishihara test, and a color recognition memory test were also administered. The color recognition memory test was performed using a basic 12-color kit displayed on a computer screen. Color recognition was evaluated after 5 and 30 min using four initial stimuli and four new colors from the 12-color kit. Participants were required to recognize which of the eight randomly presented colors they had previously seen.ResultsSignificant differences were observed in the total error scores for color recognition memory among the three groups. Medians (interquartile range) for CG, MCI, and MD groups were 2 (2), 4 (2), and 5 (3) respectively. A Kruskal–Wallis test returned a significant p-value (p < 0.001); post-hoc analysis of group pairs was then conducted for CG and MCI (p < 0.001), MCI and MD (p = 0.007), and CG and MD (p < 0.001). Using demographic information and ADAS-Cog 13 scores as predictors, a multinomial logistic regression model accurately categorized 77.9% of cases (96% of CG, 64% of MCI, and 74.1% of MD cases). Adding the color memory total error score to the model improved accuracy to 84.4% (100% of CG, 76% of MCI, and 77.8% of MD cases).ConclusionColor recognition memory test results differed significantly between participants with normal cognition and those with MCI and early AD. Therefore, it may help in the early diagnosis of AD as a simple, non-invasive diagnostic marker.